1975
DOI: 10.1161/01.cir.52.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure, sodium intake, and sodium related hormones in the Yanomamo Indians, a "no-salt" culture.

Abstract: The Yanomamo Indians are an unacculturated tribe inhabiting the tropical equatorial rain forest of northern Brazil and southern Venezuela who do not use salt in their diet. The group therefore presented an unusual opportunity to study the hormonal regulation of sodium metabolism in a culture with life-long extreme restriction of dietary sodium, with parallel observations on blood pressure. Blood pressures increased from the first to second decade but, in constrast to civilized populations, do not systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
211
2
13

Year Published

1980
1980
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(231 citation statements)
references
References 15 publications
5
211
2
13
Order By: Relevance
“…41 There is good evidence from other studies also that an increasing dietary salt intake is partly responsible for the rising incidence of hypertension. [42][43][44][45][46][47][48] Hypertension is a major health problem in this community. This study suggests that control programmes focusing on preventing obesity and identifying people with family history of hypertension might be particularly effective in reducing total cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…41 There is good evidence from other studies also that an increasing dietary salt intake is partly responsible for the rising incidence of hypertension. [42][43][44][45][46][47][48] Hypertension is a major health problem in this community. This study suggests that control programmes focusing on preventing obesity and identifying people with family history of hypertension might be particularly effective in reducing total cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate intake of these two vitamins along with vitamin B 6 reduces plasma homocysteine concentrations, an independent risk factor for CVD (Gerhard & Duell, 1999;Mann et al, 1999). Hunter-gatherers rarely if ever added salt to their foods, and studies of salt-free Yanomamo Indians have shown these indigenous people to maintain low blood pressures that do not increase with aging (Oliver et al, 1975). Finally, except for certain American Indian societies (starting about 5000 y ago), regular smoking of tobacco was unknown in huntergatherers (Eaton et al, 1988b).…”
Section: Other Environmental Factorsmentioning
confidence: 99%
“…Furthermore, a possible threshold level has not been established. There appear to be only three moderately well established points on a dose-response curve of sodium intake and blood pressure for populations: very low levels, associated with an absence of hypertension (e.g., South Pacific Islanders, Amazonian Indians), the usual levels in industrialized society, and intake over 20 g/day (e.g., the Qash' qai, Akita prefecture in northern Japan).3' 5,6,26 The Tarahumara Indians of Mexico may be a possible exception to the linear relationship inferred from those data, with an estimated intake of 2-3 g/day and an absence of elevated blood pressure, suggesting a threshold effect above the physiologic minimum.47 The data reported here support the hypothesis of a linear relationship over the range presently observed in industrial society, at least for children. Salt intake is not likely to be the sole etiologic factor; the twofold greater prevalence of hypertension among blacks in the U.S. compared with whites, without demonstrable excess salt intake, strongly suggests the interaction of multiple causes.…”
mentioning
confidence: 99%